2019
DOI: 10.1002/jor.24250
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of chronic rotator cuff healing using adipose‐derived stem cell‐seeded human tendon‐derived hydrogel

Abstract: Rotator cuff (RTC) repair outcomes are unsatisfactory due to the poor healing capacity of the tendon bone interface (TBI). In our preceding study, tendon hydrogel (tHG), which is a type I collagen rich gel derived from human tendons, improved biomechanical properties of the TBI in a rat chronic RTC injury model. Here we investigated whether adipose‐derived stem cell (ASC)‐seeded tHG injection at the repair site would further improve RTC healing. Rats underwent bilateral supraspinatus tendon detachment. Eight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 44 publications
3
36
0
1
Order By: Relevance
“…On a histological evaluation, fibrocartilage formation is known to play an important role in force transmission and energy dissipation between the 2 tissues of the tendon-to-bone interface enthesis, and fibrocartilage formation is a condition for successful tendon-to-bone interface healing. 15,16,35 In our study, HE and safranin O staining showed excellent results in the cell sheet transplantation after repair group compared with those in the other groups. Additionally, it was confirmed by histomorphological analysis that the ADSC sheet showed excellent results in fibrocartilage formation of tendon-to-bone interface healing.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…On a histological evaluation, fibrocartilage formation is known to play an important role in force transmission and energy dissipation between the 2 tissues of the tendon-to-bone interface enthesis, and fibrocartilage formation is a condition for successful tendon-to-bone interface healing. 15,16,35 In our study, HE and safranin O staining showed excellent results in the cell sheet transplantation after repair group compared with those in the other groups. Additionally, it was confirmed by histomorphological analysis that the ADSC sheet showed excellent results in fibrocartilage formation of tendon-to-bone interface healing.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have used adult stem cells, such as bone marrow, adipose, tendon, and cord blood stem cells, to treat tendon diseases. 15,31,33,44 Most studies showed the efficacy of stem cells, but there were some limitations. The most controversial point is that almost all studies have shown the effect of a single stem cell injection; thus, it is unknown how long the stem cells will remain at the repair or application site after the injection.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it was noted that an ASCs' application decreased migration and proliferation of inflammatory cells, promoted the expression of anti-inflammatory cells, and downregulated the synthesis of proinflammatory cytokines, in laboratory models [70,71] The regenerative properties of ASCs have also been examined in rotator cuff repair models [72][73][74][75][76]. It has been noted that the local application of ASCs could result in less pronounced inflammation and increased bone mineral density in histologically evaluated tissues or improved their biomechanical function [72][73][74]. However, others have reported that the subjects treated with ASCs did not benefit from its application as compared with a control group [75,76].…”
Section: Animal Modelsmentioning
confidence: 99%
“…Augmentation of chronic rotator cuff healing using adipose-derived stem cell-seeded human tendon-derived hydrogel [73] Controlled experimental study…”
Section: Animal Modelsmentioning
confidence: 99%
“…Several animal models have demonstrated cell-based approaches using MSCs can improve tendon repair, and when these studies are taken together, they improved histological and biomechanical properties of the tendons, indicating an increased rate of tendon healing and maturation [25,26]. BMC and autologous-derived stem cells have also been used in the surgical management of rotator cuff repair to augment healing [22,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%